Association of the Dundee severity classification with mortality, length of stay and readmission in adult inpatients with cellulitis. (5th October 2018) - Cutfield, Tim; Walter, Hannah; Hobbs, Mark; Chuang, Ariel; Thomas, Mark G; Ritchie, Stephen R
Abstract: Background: The Dundee classification is a simple severity assessment tool that could optimize treatment decisions and clinical outcomes in adult patients with cellulitis; however, it has not been validated in a large cohort. Objectives: To determine whether the Dundee classification reliably identified those patients with cellulitis who had a higher mortality, a longer length of hospital stay or an increased risk of readmission. Methods: We performed a retrospective study of all adults with a primary discharge diagnosis of cellulitis admitted to Auckland City Hospital from August 2013 to June 2015. We classified patients by severity using the Dundee scoring system. Results: The 30 day all-cause mortality in adult patients with a discharge diagnosis of cellulitis was 2% (29/1462) overall, and was 1% (10/806), 2% (6/271), 3% (10/353) and 9% (3/32) in Classes 1, 2, 3 and 4 of the Dundee classification, respectively ( P  =   0.01). Mortality was strongly associated with age >65 years (OR 9.37, 95% CI 3.00–41.23) and with heart failure (OR 6.16, 95% CI 2.73–14.23). There were significant associations between the Dundee classification and the incidence of bacteraemia, the length of hospital stay and the rate of readmission to hospital. Conclusions: The Dundee classification is a simple, reliable tool that can be easily applied in clinical settings to predict risk of mortality in order to determine which patients can be managed in the community with oral or intravenous therapy, and which require inpatient care.